Mapping the research of nursing in Parkinson’s disease: a bibliometric and quantitative analysis - Liao, Han-Bing; Fang, Yan-Lin; Chen, Shu-Yi; Yin, Yu-Shan; Li, Jiao; Zhou, Peng; Li, Bin; Jiang, Xing-Zuan; Lei, Ying-Fang (Frontiers in Neurology, 2024)
Background Parkinson’s disease (PD) is a chronic and progressive neurodegenerative disorder. Clinically, the therapeutic strategy of PD could only alleviate the symptoms. Nursing plays a crucial role in providing patient education, symptom management, and psychosocial support. This study aims to analyze the current state and prospects of research in the field of Parkinson’s disease (PD) and its associated nursing care through bibliometric methods to explore the trends that May guide its future development. Methods Literature related to Parkinson’s disease and nursing care was systematically searched by the Web of Science database from 1991 to 2023. Quantitative analysis of cooperative networks was conducted using bibliometric tools VOSviewer and CiteSpace. Results The analysis covered 2,649 publications in the field of PD and nursing care, authored by 12,576 researchers from 3,869 institutions across 94 countries. The number of articles has steadily increased over the past 20 years. In this research field, the United States and the United Kingdom emerged as leading countries, and Radboud Universiteit Nijmegen was positioned as an international hub. Movement Disorders was identified as the journal with the highest output and with the most co-citation. Prof. Bastiaan R. Bloem published the most papers in the area, and Prof. Per Odin had the highest average citation. The major fields of these publications are clinical neurology, geriatrics & gerontology, multidisciplinary sciences, and health care sciences & services. Hot topics in the field predominantly revolve around Parkinson’s disease, quality of life, and dementia. Conclusion Research in Parkinson’s disease and nursing care is experiencing a period of rapid growth, with continuous expansion in research scope and depth of investigation. One of the trends identified is the increasing focus on quality of life and the management of dementia in PD patients, reflecting the importance of these areas in research. The study further suggests that future advancements in the field May rely significantly on strengthening international collaborations and addressing global disparities in resource distribution, particularly by promoting research inclusivity and cooperation among low-resource countries.